Blindness and Social Media in India - Thankam Varghese, Soumya; Maya Rathnasabapathy, Dr (International Journal of Engineering and Technology, 2018)
In the present world, social networking sites offer a great platform to communicate, collaborate and socialize â€“ personally and professionally with the world around us. According to WHO report, blind people are a significant group comprising 45 million totally blind and 285 million partially blind. This paper reviewing studies on the non (use) of social media by blind people in and out India. It examines the impediments, achievements and expectations of blind people with regard to social network sites based on past research work.Â